Irradiation aging of the CMS Drift Tube muon detector. (July 2020) - Ferrero, D.D. Redondo; Abbiendi, G.; Maestre, J. Alcaraz; Fernández, A. Álvarez; González, B. Álvarez; Amapane, N.; Bachiller, I.; Barcala, J.M.; Barcellan, L.; Battilana, C.; Bellato, M.; Bencze, G.; et al.
Abstract: During the High Luminosity LHC, the Drift Tube chambers installed in the CMS detector need to operate with an integrated dose ten times higher than expected at the LHC due to the increase in integrated luminosity from 300 fb -1 to 3000 fb -1 . Irradiations have been performed to assess the performance of the detector under such conditions and to characterize the radiation aging of the detector. The presented analysis focuses on the behaviour of the high voltage currents and the dose measurements needed to extrapolate the results to High Luminosity conditions, using data from the photon irradiation campaign at GIF++ in 2016 as well as the efficiency analysis from the irradiation campaign started in 2017. Although the single-wire loss of high voltage gain observed of 70% is very high, the muon reconstruction efficiency is expected to decrease less than 20% during the full duration of High Luminosity LHC in the areas under highest irradiation. Highlights: The High Luminosity Large Hadron Collider will have increased radiation levels. Exposure to radiation reduces the performance of gaseous detectors. Drift Tube detectors are being characterized for future operation.